Record of enhanced late Pliocene tectono‐volcanic activity in the Lesser Antilles forearc basin: Insights into the long‐term behaviour of the Lesser Antilles subduction zone. (8th June 2017) - Léticée, Jean‐Len; Philippon, Mélody; Cornée, Jean‐Jacques; Münch, Philippe; De Min, Lyvane; Noury, Mélanie; Randrianasolo, Auran; Lebrun, Jean‐Frédéric
Abstract: In this study, we investigate the Lesser Antilles forearc basin, focusing on the late Pliocene to Pleistocene sedimentary archives in order to track the occurrence of extreme events triggered by enhanced subduction‐related tectono‐volcanic activity. We identify late Piacenzian deposits covering a major regional erosional surface, displaying sedimentary dykes and large marine boulders embedded in a mixed continental–marine matrix, characteristic of tsunamites. We interpret this episode of platform emersion and the successive cataclysmic deposits as resulting from enhanced tectonic activity at the interface of the subduction zone, synchronous with the initiation of the Lesser Antilles volcanic arc. We then discuss the implications in terms of the mechanical behaviour of the Lesser Antilles subduction zone.